Religious Moderation as a Pillar of Tolerance in Multicultural Indonesia - Hidayati, Ratna; Majduddin, Mohammad; Said, Imam Ghazali (Electronic Journal of Education, Social Economics and Technology, 2025)
Religious moderation is a strategic approach to strengthen the spirit of tolerance for the creation of an inclusive and peaceful society in a multicultural country like Indonesia to face the great challenge of maintaining social harmony in the midst of religious, cultural, and ethnic diversity. This qualitative research aims to examine the basic concept of religious moderation and its role in the formation of tolerance attitudes in Indonesia's multicultural society and the extent of the implementation of religious moderation values in the practice of social life and public policy. Through a literature analysis, this study found that religious moderation is not just a theological middle stance, but a social construct that encourages fairness, respects differences, and prevents extremism. This concept plays a crucial role in forming social cohesion and encouraging interfaith interaction based on mutual understanding and respect. The results of the study show that the implementation of religious moderation still needs strengthening, both through education, regulations, and the active role of religious leaders and the government. These findings are expected to contribute to formulating strategies to strengthen tolerance in multicultural Indonesia.